A review of commercially available thrombin generation assays. Issue 1 (16th October 2017) - Kintigh, Jeremy; Monagle, Paul; Ignjatovic, Vera
Abstract: Essentials Overview of the three commercial thrombin generation methods. Description of the sample preparation, data management, and analysis. Description of the similarities and differences in regards to substrates results. Discussion of advantages and disadvantages of the three approaches. Currently there are three commercially available thrombin generation methods. These methods help detect the levels of thrombin generated in patient samples by the use of chromogenic or fluorogenic substrates in plasma or whole blood. Determining the rate of thrombin generation can help indicate if patients are at risk of clotting or bleeding. This review discusses two fluorogenic and one chromogenic method and focuses on similarities and differences of these three methods. The review specifically focuses on the accuracy of commercial substrates used in thrombin generation, and interference that can occur by various plasma proteins, as well as on evaluating the advantages and disadvantages of each method. The commercial chromogenic assay and both fluorogenic assays are able to monitor the rate of thrombin generation and can give indications towards potential coagulation abnormalities. Overall, the main differences between the thrombin generation methods are based on the type of substrate used, sample preparation, and data processing. Despite advancement in this field there are still technical challenges that preclude the widespread use of thrombin generation in clinical applications.